Sensitivity analysis of InfoCrop model for Indian-mustard varieties in western Haryana - Yogesh Kumar,; Raj Singh,; Anil Kumar,; Sagar Kumar, (Journal of Oilseed Brassica, 2026)
An InfoCrop model was validated with data sets generated on three varieties of Brassica juncea viz. Kranti,RH 406 and RH 0749 through field experiment laid in split plot design with three sowing dates of Rabi 2014-15 viz. 25th October, 5th November and 15th November, respectively. In sensitivity analysis, differentcombinations of maximum and minimum temperature, seasonal rainfall and elevated CO2 concentration weresimulated which reflected a substantial change in seed yield. A change of ± 10C in daily maximum andminimum temperatures led to increase in seed yield over base yield. The simulation results also supported theincrease in seed yield in all three varieties due increase in the seasonal rainfall by 10 to 20%. Further,elevation in CO2 concentration up to 490 ppm at constant temperature resulted in 13–32% also showedincrement in seed yield of mustard; however, further increase in CO2 concentration beyond 490 ppm adverselyaffected the seed yield all three varieties.